Durable Response of Dabrafenib, Trametinib, and Capmatinib in an NSCLC Patient With Co-Existing BRAF-KIAA1549 Fusion and MET Amplification: A Case Report - Chou, Yun-Tse; Lin, Chien-Chung; Lee, Chung-Ta; Pavlick, Dean C.; Su, Po-Lan (Frontiers in Oncology, 2022)
BRAF fusions are rare driver oncogenes in non-small cell lung cancer (NSCLC). Similar with BRAF V600E mutation, it could also activate the MAPK signaling pathway. There are a few case reports which had indicated the potential response to BRAF inhibitors and its important role as de novo driver mutation. In addition, the co-occurring MET amplification has been defined as a poor prognostic factor in patients with epidermal growth factor receptor (EGFR) mutant NSCLC. Currently, there are ongoing clinical trials which investigate the MET amplification as a therapeutic target in patients with EGFR mutant NSCLC and acquired resistance to osimertinib, which imply that the MET amplification also had a therapeutic significance. However, the co-occurring MET amplification had not been studied in patients with BRAF fusion before. A 67-year-old man was diagnosed with metastatic poorly-differentiated adenocarcinoma. He received first-line therapy with the combination of pembrolizumab and chemotherapy because the genomic test revealed wild-type EGFR, and negativity of ALK and ROS1 by immunohistochemical stain. Upon disease progression, the next-generation sequencing revealed co-occurring KIAA1549-BRAF fusion and MET amplification. Subsequent dabrafenib, trametinib, and capmatinib combination therapy showed a remarkable treatment effect. The combination therapy targeting the co-occurring driver mutations is a potential effective treatment for NSCLC patients. Further prospective study is still warranted to investigate the role of co-occurring driver mutations and the relevant treatment strategy.